GE_GERICHTE C/26188/2015 vom 23. Mai 2016 - GE Cour de justice (2016)
ÉVACUATION(EN GÉNÉRAL); CAS CLAIR; LOCATAIRE; DÉFAUT DE PAIEMENT; SOMMATION; PRINCIPE DE LA RÉCEPTION | CO.257d; CPC.257; CO.257c; CCR.1